MASALAH-MASALAH SOSIAL DALAM KUMPULAN CERPEN CEMARA KARYA HAMSAD RANGKUTI - Putra, Oji Tri Ananda; Hayati, Yenni; Nasution, Muhammad Ismail (Universitas Negeri Padang, 2019)
This article aims to describe social problems in the collection of short Cemara by Hamsad Rangkuti. The data in this study are words, phrases, clauses, or sentences that contain the discourse of social problems in the collection of short Cemara by Hamsad Rangkuti. The source of the data in this study is the short-short story in a collection of short Cemara by Hamsad Rangkuti. In this short story collection has 15 titles of short stories, but only 12 short story from which the data in this study. Data that has been entered into the tables collected inventory data to obtain summary data. The results showed that in a collection of short Cemara by Hamsad Rangkuti indeed found the existence of problems that are contained on each short story that became a source of research. Aspects of social issues contained in a collection of short stories this is a form, causes, and the impact of social issues. Causes of social problems in the collection of short stories include the economical factors, biological, cultural, and bio-psychology, but not bio-psychology many factors were discovered. In a few short stories that became a source of research, there is a form of deviant behavior and social inequalities that clearly reflected the author's way of building character stories and figures according to the theme that many raised issues of life in the social community.Keywords: social problems, the collection of short Cemara by Hamsad Rangkuti